Peranan ACE-Inhibitor pada penyakit jantung bawaan - Yusra Pintaningrum; Alit Utamayasa; Mahrus A. Rahman; Teddy Ontoseno; Ketut Angga Aditya Putra Pramana (Sasambo Journal of Pharmacy, 2023)
Angiotensin-converting enzyme inhibitors have been shown to have the broadest impact of any drug in cardiovascular medicine. Dual role of ACE inhibitors, both preventing and treating cardiovascular disease. ACE inhibitors have an indirect effect on primary prevention by lessening hypertension and decreasing left ventricular hypertrophy, especially in patients with cardiac failure. In children, the causes of cardiac failure are significantly different and many cases are due to congenital malformations, such as left-to-right- shunts. In these patients, the function of both the right and the left ventricles will be affected and these children suffer from high-output cardiac failure. Therefore, in carefully selected patients with congenital heart disease, the response to systemic afterload reduction with ACE inhibitors appears favorable. Nevertheless, a more comprehensive controlled trial to assess the hemodynamic and functional effects of ACE inhibitors in such patients should be undertaken.